Pojęcie prawnych form działania administracji - Kijowski, Dariusz R. (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The study proposes a definition of a conceptual category of a “legal form of administrative action”, its rationale, and a critical reference to the way this legal term is understood in the doctrine. It also indicates the practical importance of a proper formulation of this problem.
Keywords: inactivity of administration; manifestations of activities; activities of public administration; external manifestations of activity; public tasks; silence of public administration; factual activities; forms of action; public administration